Revenge of the living dummy - Stine, R. L. (Stine, R. L. Goosebumps HorrorLand, 2008)
Britney Crosby is tormented by her cousin Ethan and his ventriloquist's dummy, but she soon learns that the puppet itself has plans of its own. Next, a lucky someone is offered a free week at a theme park known as "HorrorLand," but soon realizes that not all guests are allowed to leave.